Academic Performance Indices: Error Calculation in Distributed MPP Tracking using PID and FLC - Sharma, Chandani; Jain, Anamika (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*278.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967464);" role="presentation">The extensive use of PV panels in Distributed and Renewable Electricity Generation is significantly driving <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*291.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960884);" role="presentation">Green energy revolution globally. The core of Distributed generation i.e. maximization of power output from <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*304.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935601);" role="presentation">panels is being propelled by Maximum Power Point Trackers. However, fully tracked systems with outputs 40- <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*318.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978648);" role="presentation">45% can be made to accomplish reduced loss with determination of errors. This includes convergence of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98016);" role="presentation">iterative output <span dir="ltr" style="left: calc(var(--scale-factor)*142.10px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928518);" role="presentation">sequences for <span dir="ltr" style="left: calc(var(--scale-factor)*206.21px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927303);" role="presentation">distributed <span dir="ltr" style="left: calc(var(--scale-factor)*254.81px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950705);" role="presentation">temperature and irradiance <span dir="ltr" style="left: calc(var(--scale-factor)*374.59px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99182);" role="presentation">functions. Different <span dir="ltr" style="left: calc(var(--scale-factor)*462.78px); top: calc(var(--scale-factor)*331.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02222);" role="presentation">sets of tuning <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*344.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927573);" role="presentation">parameters based on academic performance indices for PID and FLC are investigated in this paper. These are <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*357.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970215);" role="presentation">optimized through MATLAB/SIMULINK to obtain converter output close to the desired with minimum error. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919579);" role="presentation">The analysis of <span dir="ltr" style="left: calc(var(--scale-factor)*136.34px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927147);" role="presentation">Integral of Squared Error (<span dir="ltr" style="left: calc(var(--scale-factor)*244.37px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932703);" role="presentation">ISE), <span dir="ltr" style="left: calc(var(--scale-factor)*267.89px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945278);" role="presentation">Integral of Absolute Error (<span dir="ltr" style="left: calc(var(--scale-factor)*378.91px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02889);" role="presentation">IAE), <span dir="ltr" style="left: calc(var(--scale-factor)*404.11px); top: calc(var(--scale-factor)*371.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961952);" role="presentation">Integral of time multiplied by <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928029);" role="presentation">Squared Error (<span dir="ltr" style="left: calc(var(--scale-factor)*137.66px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953244);" role="presentation">ITSE) <span dir="ltr" style="left: calc(var(--scale-factor)*166.22px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*184.85px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99919);" role="presentation">Integral of time multiplied by Absolute Error (<span dir="ltr" style="left: calc(var(--scale-factor)*382.99px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0584);" role="presentation">ITAE) <span dir="ltr" style="left: calc(var(--scale-factor)*413.23px); top: calc(var(--scale-factor)*384.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970995);" role="presentation">is carried out on validated <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*397.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971515);" role="presentation">model (PID as well as FLC). A <span dir="ltr" style="left: calc(var(--scale-factor)*206.81px); top: calc(var(--scale-factor)*397.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944861);" role="presentation">comparative study for <span dir="ltr" style="left: calc(var(--scale-factor)*300.55px); top: calc(var(--scale-factor)*397.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934207);" role="presentation">both models is presented in the paper. <span dir="ltr" style="left: calc(var(--scale-factor)*462.10px); top: calc(var(--scale-factor)*397.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9471);" role="presentation">The simulation <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88771);" role="presentation">results <span dir="ltr" style="left: calc(var(--scale-factor)*101.18px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920517);" role="presentation">shown in the present paper confirms that <span dir="ltr" style="left: calc(var(--scale-factor)*270.17px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*285.53px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970598);" role="presentation">errors (ISE, IAE, ITSE and ITAE) <span dir="ltr" style="left: calc(var(--scale-factor)*428.98px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930939);" role="presentation">are minimized <span dir="ltr" style="left: calc(var(--scale-factor)*489.94px); top: calc(var(--scale-factor)*410.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93126);" role="presentation">even for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*423.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897151);" role="presentation">changing temperature and irradiance and the best results are obtained using an FLC <span dir="ltr" style="left: calc(var(--scale-factor)*409.39px); top: calc(var(--scale-factor)*423.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880458);" role="presentation">system. T<span dir="ltr" style="left: calc(var(--scale-factor)*448.54px); top: calc(var(--scale-factor)*423.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889277);" role="presentation">he model designed <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*437.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921071);" role="presentation">is intended to be beneficial source for PV engineers and researchers to <span dir="ltr" style="left: calc(var(--scale-factor)*364.39px); top: calc(var(--scale-factor)*437.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961373);" role="presentation">provide high efficiency with the use of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*450.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980379);" role="presentation">MPPT.